The Right to Work as a Fundemantal Human Right - Kaya, Pir Ali; Yilmazer, Isin Ulas Ertugrul (European Scientific Journal, ESJ, 2019)
The right to work is a fundamental human right ensuring that every individual shall be able to continue their lives with a desired job and an income allowing the protection of human dignity. The right to work is directly related with the right to live of the working class that tries to live on their labor. Therefore, the right to work is the quest for a right based on life under a social order allowing every individual to have a job and income for continuing their lives in addition to protecting their dignity while allowing personal development and individual freedom. In this view, this study is based on the right to work which is a fundamental human right has been taken into consideration from the international human rights law perspective. Because of that firstly the concept of human rights and its historical development have been underlined. After then, it wants to take attention to emphasize of work right in concept of human rights. In this context, demand right to be employed, working right at a job which freely gained, the right to protection against the termination of labour contract and the right to use of freedom of association and union rights have been discussed.